Summit Diplomacy under Jokowi Governance: Revealing the Implementation and National Interest in ASEAN Summit - Jelita Eka Azzahra; Nhat Minh Bui (Dauliyah: Journal of Islam and International Affairs, 2025)
The rapid development of today’s era due to advancement of science and technology also the increasement of world dynamic complexity has driven ramification of diplomacy concept that promote summit diplomacy. As Jokowi reputation bolstered up since Indonesia successfulness to run G20 presidency and contribute to many summits without marginalizing diplomats’ roles, the highlight discussion enhanced to practice of Indonesia summit diplomacy towards ASEAN since it always be cornerstone of Indonesia foreign policy in line with ASEAN Chairmanship 2023. Within case of ASEAN Summit and ASEAN + EU Summit in 2022 particularly, this research aimed to answer how’s the implementation of Indonesia summit diplomacy under Jokowi administration which applicated Ku framework of summit diplomacy by using Lamount qualitative approach. The result shown that first discussed leaders as performer, Jokowi is able to perform impressively during ASEAN summit regardless his background, Summitry activities and diplomatic whereas under his leadership the summit is addressed to enhance relations and cooperation to achieve common interest with bringing Indonesia goals, media control that informed expansively the result of summit and portray Jokowi as appreciation towards his work for Indonesian and ASEAN people and last Collaborating with Other States as Joint Production reflected from Jokowi intensively encouragement that succeed enhancement of ASEAN-EU cooperation. To support this study, data is obtained from primary resources from declaration, formal report etc., with support secondary sources including textbook, articles and literature reviews. The main outcomes indicate a well implemented Jokowi’s summit diplomacy that highlight national interest amidst international agenda.